Correction to: The patient advisor, an organizational resource as a lever for an enhanced oncology patient experience (PAROLEonco): a longitudinal multiple case study protocol - M. P. Pomey; M. de Guise; M. Desforges; K. Bouchard; C. Vialaron; L. Normandin; M. Iliescu-Nelea; I. Fortin; I. Ganache; C. Régis; Z. Rosberger; D. Charpentier; et al. (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.